INFLUENCE OF BIODIESEL ON PERFORMANCE OF MACHINE-TRACTOR UNITS. - Nadykto, Volodymyr; Findura, Pavol; Kiurchev, Volodymyr; Orel, Oleksandr; Надикто, Володимир Трохимович; Кюрчев, Володимир Миколайович; Орел, Олександр Миколайович (Slovaca Universitas Agriculturae Nitriae, 2022)
Currently, liquid biofuels, and especially biodiesel, are increasingly used. In terms of agricultural production, there arises an urgent question whether utilization of biofuels in agricultural tractors is feasible and efficient. Majority of results regarding the biodiesel use comes from bench tests of engines. However, work of any machine-tractor unit under real conditions, except for the steady- state mode of movement, includes acceleration mode after a turn, or after it was forced stop in the field. It has been established that the addition of sunflower methyl ester (SME) into conventional diesel (CD) leads to a decrease in the throttle response of a tractor engine during its field operation. Using 50% CD and 50% SME as fuel mixture, the tillage machine-tractor unit’s acceleration time increased by 16.6%. Operating on SME only, the unit’s acceleration time reached 50%. The acceleration process of a machine- tractor unit using fuel with addition of SME is non-linear. It consists of two parts: more intensive − with SME content in diesel fuel of up to 50%, and less intensive − with an increase in SME proportion over 50%. When using a mixture of CD with SME in a ratio of 50 : 50, the soil cultivation machine-tractor unit performance decreased by 7.2%, and fuel consumption per tilled area increased by 5.3%.
Keywords: conventional diesel; biodiesel; sunflower methyl ester; throttle response